Dry storage of multiple reagent types within a paper microfluidic device for phenylalanine monitoring. Issue 5 (19th January 2021) - Wentland, Lael; Polaski, Rachel; Fu, Elain
Abstract : Demonstration of robust reagent stability for three types of reagents in a phenylalanine monitor. Abstract : The degradation of biochemical reagents on the timescale of weeks can severely limit the utility of microfluidic assays intended for field use, and is a challenging aspect of microfluidic device development in general. Our study focuses on the evaluation of the dry storage stability of three types of reagents: (i) the colorimetric reagents nitroblue tetrazolium and 1-methoxy-5-methylphenazinium methylsulfate, (ii) the enzyme phenylalanine dehydrogenase, and (iii) the coenzyme β-nicotinamide adenine dinucleotide hydrate, within the context of a phenylalanine monitoring device. We have demonstrated stable dry storage of each of the reagents, over the time span of approximately one month. Drying the colorimetric reagents under nitrogen was found to largely suppress reagent degradation and the appearance of nonspecific signal, while the enzyme and coenzyme retained activity when stored dry for a month without additional processing or chemical additives. Finally, phenylalanine monitoring devices with all three reagent types dried down and stored for 15 days showed comparable functionality to devices containing freshly-dried reagents – a key milestone to enable future clinical testing.